Método Monte Carlo e suas aplicações - Carvalho, Admilson Rodrigues de (2017)
The Mathematics has been an important tool used by the humankind since the ancient times. From the first problems involving simple counting of objects to the development of refined and advanced technology theories. The Mathematics has become indispensable to our own development, mainly to predict random-nature, probabilistic or intuitive phenomena, which are present in the universe. In Basic, Technical and Technological Education, teachers hope that students use Mathematics in a logical way to solve everyday problems. Thus, the main aim of this paper is to present through an approach of the Monte Carlo Method that this Method has many applications in several areas of Science, especially in the area calculation with no need of previous knowledge of integral calculation. Firstly, the theories of probability and random variables were reviewed together with their main definitions, theorems and properties. Then, I approached the Monte Carlo Method and its applications, which may be the reference to be exploited in Mathematics Education by teachers and learners.